A carbon nitride supported copper nanoparticle composite: a heterogeneous catalyst for the N-arylation of hetero-aromatic compounds. (21st March 2017) - Nandi, Debkumar; Siwal, Samarjeet; Mallick, Kaushik
Abstract : Copper nanoparticle catalyzed N -arylation of hetero-aromatic molecules. Abstract : A graphitic carbon nitride supported copper nanoparticle composite (Cu–gCN) has been found to be an active catalyst for the N -arylation of hetero-aromatic systems (pyrrole, pyrazole, and substituted indole) and benzamide molecules, with high product selectivity and good to excellent yields, using substituted aryl bromide as a coupling partner. The intercalated structure and the amine functional group of the carbon nitride prevent the aggregation of the catalytically active copper species during the reaction, and the recyclability study shows the stable performance of the catalyst without a significant loss of catalytic activity.